The development of purifying technology of process waters of gas condensate field from methanol; Bulletin of the Tomsk Polytechnic University; Vol. 311, № 3 - Brenchugina M. V.; Buinovsky (Buynovskiy, Buinovskii) A. S. Alexander Sergeevich; Ismagilov Z. R.; Kuznetsov V. V. (Chemistry, 2007)
Заглавие с титульного листа